Struktur Sukuk dan Dinamika Pasar : Analisis Peran dan Dampaknya Dalam Pasar Modal Syariah (studi kasus pasar modal Syariah) - Linda Agustina Saputri; Khairina Nur Shadrina; M.Erbi Farel.K.H; Farida Asfiah; Ersi Sisdianto (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The concept of Islamic sharia-based finance is currently growing very rapidly and is a good alternative for the market to realize sharia compliance. The capital market is defined as a meeting place between supply and demand for securities (Soemitra, 2014). The market which is known as the conventional capital market is considered not conducive to the Islamic financial system due to the very high interest rates and speculation in it.Sukuk is a form of instrument used for investment which has been widely issued by both corporations and countries. In many cases, dynamics is the most important decision variable taken by companies and competitors. Market dynamics is a movement in which a company can achieve sales targets resulting from product purchases by buyers.